Can we solve $A+Dsin^2x=Bsin x+Ccos x$ without having to solve a quartic polynomial?

The name of the pictureThe name of the pictureThe name of the pictureClash Royale CLAN TAG#URR8PPP











up vote
4
down vote

favorite
2












Suppose the following equation
$$
A+Dsin^2x=Bsin x+Ccos x,
$$
where $A,B,C,DinmathbbR$ are the real constants. Initially, I tried to find its solution from a simple substitution
beginalign*
A-Bsin x+Dsin^2x & =pm Csqrt1-sin^2x,
endalign*
that after $t=sin x$ leads to the following quartic equation
$$
(A^2-C^2)-2ABt+(B^2+2AD+C^2)t^2-2BDt^3+D^2t^4=0.
$$
The Weierstrass substitution, where $t=tanfracx2$, and
$$
sin x=2sinfracx2cosfracx2=frac2sinfracx2cosfracx2cos^2fracx2=frac2tanfracx2frac1cos^2fracx2=frac2tanfracx21+tan^2fracx2=frac2t1+t^2,
$$
and
$$
cos x=cos^2fracx2-sin^2fracx2=left(1-fracsin^2fracx2cos^2fracx2right)cos^2fracx2=frac1-tan^2fracx2frac1cos^2fracx2=frac1-tan^2fracx21+tan^2fracx2=frac1-t^21+t^2,
$$
leads to
$$
A+Dfrac4t^2(1+t^2)^2=Bfrac2t1+t^2+Cfrac1-t^21+t^2,
$$
which is also the quartic equation for $t$
$$
(A+C)t^4-2Bt^3+2(A+2D)t^2-2Bt+A-C=0,
$$
$$
(A+C)t^4-2Bt(t^2+1)+2(A+2D)t^2+A-C=0.
$$
Is there any better substitution avoiding the transformation of the trigonometric identity to the quartic equation for $t$?



Thanks for your help.







share|cite|improve this question





















  • $beginalign* A-Bsin x+Dsin^2x & = pm Csqrt1-sin^2x endalign* not = Csqrt1-sin^2x$
    – S.H.W
    18 hours ago











  • @ S.H.W: thanks, corrected
    – justik
    15 hours ago










  • Note that $A+Bsin^2 x$ can be written as $P + Qcos 2x$ for appropriate $P$ and $Q$; also, $B sin x + C cos x$ can be written as $M sin(x + N)$ for appropriate $M$ and $N$. Considering how a "$cos 2x$" wave and a "$sin(x+N)"$ wave look, it seems reasonable to expect/fear that —barring some special relationships among the coefficients— the curves will meet in four asymmetric points.
    – Blue
    12 hours ago















up vote
4
down vote

favorite
2












Suppose the following equation
$$
A+Dsin^2x=Bsin x+Ccos x,
$$
where $A,B,C,DinmathbbR$ are the real constants. Initially, I tried to find its solution from a simple substitution
beginalign*
A-Bsin x+Dsin^2x & =pm Csqrt1-sin^2x,
endalign*
that after $t=sin x$ leads to the following quartic equation
$$
(A^2-C^2)-2ABt+(B^2+2AD+C^2)t^2-2BDt^3+D^2t^4=0.
$$
The Weierstrass substitution, where $t=tanfracx2$, and
$$
sin x=2sinfracx2cosfracx2=frac2sinfracx2cosfracx2cos^2fracx2=frac2tanfracx2frac1cos^2fracx2=frac2tanfracx21+tan^2fracx2=frac2t1+t^2,
$$
and
$$
cos x=cos^2fracx2-sin^2fracx2=left(1-fracsin^2fracx2cos^2fracx2right)cos^2fracx2=frac1-tan^2fracx2frac1cos^2fracx2=frac1-tan^2fracx21+tan^2fracx2=frac1-t^21+t^2,
$$
leads to
$$
A+Dfrac4t^2(1+t^2)^2=Bfrac2t1+t^2+Cfrac1-t^21+t^2,
$$
which is also the quartic equation for $t$
$$
(A+C)t^4-2Bt^3+2(A+2D)t^2-2Bt+A-C=0,
$$
$$
(A+C)t^4-2Bt(t^2+1)+2(A+2D)t^2+A-C=0.
$$
Is there any better substitution avoiding the transformation of the trigonometric identity to the quartic equation for $t$?



Thanks for your help.







share|cite|improve this question





















  • $beginalign* A-Bsin x+Dsin^2x & = pm Csqrt1-sin^2x endalign* not = Csqrt1-sin^2x$
    – S.H.W
    18 hours ago











  • @ S.H.W: thanks, corrected
    – justik
    15 hours ago










  • Note that $A+Bsin^2 x$ can be written as $P + Qcos 2x$ for appropriate $P$ and $Q$; also, $B sin x + C cos x$ can be written as $M sin(x + N)$ for appropriate $M$ and $N$. Considering how a "$cos 2x$" wave and a "$sin(x+N)"$ wave look, it seems reasonable to expect/fear that —barring some special relationships among the coefficients— the curves will meet in four asymmetric points.
    – Blue
    12 hours ago













up vote
4
down vote

favorite
2









up vote
4
down vote

favorite
2






2





Suppose the following equation
$$
A+Dsin^2x=Bsin x+Ccos x,
$$
where $A,B,C,DinmathbbR$ are the real constants. Initially, I tried to find its solution from a simple substitution
beginalign*
A-Bsin x+Dsin^2x & =pm Csqrt1-sin^2x,
endalign*
that after $t=sin x$ leads to the following quartic equation
$$
(A^2-C^2)-2ABt+(B^2+2AD+C^2)t^2-2BDt^3+D^2t^4=0.
$$
The Weierstrass substitution, where $t=tanfracx2$, and
$$
sin x=2sinfracx2cosfracx2=frac2sinfracx2cosfracx2cos^2fracx2=frac2tanfracx2frac1cos^2fracx2=frac2tanfracx21+tan^2fracx2=frac2t1+t^2,
$$
and
$$
cos x=cos^2fracx2-sin^2fracx2=left(1-fracsin^2fracx2cos^2fracx2right)cos^2fracx2=frac1-tan^2fracx2frac1cos^2fracx2=frac1-tan^2fracx21+tan^2fracx2=frac1-t^21+t^2,
$$
leads to
$$
A+Dfrac4t^2(1+t^2)^2=Bfrac2t1+t^2+Cfrac1-t^21+t^2,
$$
which is also the quartic equation for $t$
$$
(A+C)t^4-2Bt^3+2(A+2D)t^2-2Bt+A-C=0,
$$
$$
(A+C)t^4-2Bt(t^2+1)+2(A+2D)t^2+A-C=0.
$$
Is there any better substitution avoiding the transformation of the trigonometric identity to the quartic equation for $t$?



Thanks for your help.







share|cite|improve this question













Suppose the following equation
$$
A+Dsin^2x=Bsin x+Ccos x,
$$
where $A,B,C,DinmathbbR$ are the real constants. Initially, I tried to find its solution from a simple substitution
beginalign*
A-Bsin x+Dsin^2x & =pm Csqrt1-sin^2x,
endalign*
that after $t=sin x$ leads to the following quartic equation
$$
(A^2-C^2)-2ABt+(B^2+2AD+C^2)t^2-2BDt^3+D^2t^4=0.
$$
The Weierstrass substitution, where $t=tanfracx2$, and
$$
sin x=2sinfracx2cosfracx2=frac2sinfracx2cosfracx2cos^2fracx2=frac2tanfracx2frac1cos^2fracx2=frac2tanfracx21+tan^2fracx2=frac2t1+t^2,
$$
and
$$
cos x=cos^2fracx2-sin^2fracx2=left(1-fracsin^2fracx2cos^2fracx2right)cos^2fracx2=frac1-tan^2fracx2frac1cos^2fracx2=frac1-tan^2fracx21+tan^2fracx2=frac1-t^21+t^2,
$$
leads to
$$
A+Dfrac4t^2(1+t^2)^2=Bfrac2t1+t^2+Cfrac1-t^21+t^2,
$$
which is also the quartic equation for $t$
$$
(A+C)t^4-2Bt^3+2(A+2D)t^2-2Bt+A-C=0,
$$
$$
(A+C)t^4-2Bt(t^2+1)+2(A+2D)t^2+A-C=0.
$$
Is there any better substitution avoiding the transformation of the trigonometric identity to the quartic equation for $t$?



Thanks for your help.









share|cite|improve this question












share|cite|improve this question




share|cite|improve this question








edited 15 hours ago
























asked 23 hours ago









justik

22528




22528











  • $beginalign* A-Bsin x+Dsin^2x & = pm Csqrt1-sin^2x endalign* not = Csqrt1-sin^2x$
    – S.H.W
    18 hours ago











  • @ S.H.W: thanks, corrected
    – justik
    15 hours ago










  • Note that $A+Bsin^2 x$ can be written as $P + Qcos 2x$ for appropriate $P$ and $Q$; also, $B sin x + C cos x$ can be written as $M sin(x + N)$ for appropriate $M$ and $N$. Considering how a "$cos 2x$" wave and a "$sin(x+N)"$ wave look, it seems reasonable to expect/fear that —barring some special relationships among the coefficients— the curves will meet in four asymmetric points.
    – Blue
    12 hours ago

















  • $beginalign* A-Bsin x+Dsin^2x & = pm Csqrt1-sin^2x endalign* not = Csqrt1-sin^2x$
    – S.H.W
    18 hours ago











  • @ S.H.W: thanks, corrected
    – justik
    15 hours ago










  • Note that $A+Bsin^2 x$ can be written as $P + Qcos 2x$ for appropriate $P$ and $Q$; also, $B sin x + C cos x$ can be written as $M sin(x + N)$ for appropriate $M$ and $N$. Considering how a "$cos 2x$" wave and a "$sin(x+N)"$ wave look, it seems reasonable to expect/fear that —barring some special relationships among the coefficients— the curves will meet in four asymmetric points.
    – Blue
    12 hours ago
















$beginalign* A-Bsin x+Dsin^2x & = pm Csqrt1-sin^2x endalign* not = Csqrt1-sin^2x$
– S.H.W
18 hours ago





$beginalign* A-Bsin x+Dsin^2x & = pm Csqrt1-sin^2x endalign* not = Csqrt1-sin^2x$
– S.H.W
18 hours ago













@ S.H.W: thanks, corrected
– justik
15 hours ago




@ S.H.W: thanks, corrected
– justik
15 hours ago












Note that $A+Bsin^2 x$ can be written as $P + Qcos 2x$ for appropriate $P$ and $Q$; also, $B sin x + C cos x$ can be written as $M sin(x + N)$ for appropriate $M$ and $N$. Considering how a "$cos 2x$" wave and a "$sin(x+N)"$ wave look, it seems reasonable to expect/fear that —barring some special relationships among the coefficients— the curves will meet in four asymmetric points.
– Blue
12 hours ago





Note that $A+Bsin^2 x$ can be written as $P + Qcos 2x$ for appropriate $P$ and $Q$; also, $B sin x + C cos x$ can be written as $M sin(x + N)$ for appropriate $M$ and $N$. Considering how a "$cos 2x$" wave and a "$sin(x+N)"$ wave look, it seems reasonable to expect/fear that —barring some special relationships among the coefficients— the curves will meet in four asymmetric points.
– Blue
12 hours ago











1 Answer
1






active

oldest

votes

















up vote
1
down vote













If you set $X=cos x$ and $Y=sin x$, the equation becomes geometrically finding the intersection of $DY^2-CX-BY-A=0$ (a parabola when $Dne0$), with the circle $X^2+Y^2=1$, which generally has four solutions. So, no: you can't reduce the resolvent equation from degree $4$ unless there is some particular relation between the coefficients.



If $D=0$ the problem becomes intersecting a line (provided one among $B$ and $C$ is nonzero) with a circle and indeed can be reduced to a quadratic equation.



It's no better if you use $A=Acos^2x+Asin^2x$, because the conic becomes
$$
AX^2+(A-D)Y^2+CX+BY=0
$$
which is either an ellipse, for $A(A-D)>0$, or a hyperbola, for $A(A-D)<0$.



Another way to see it is setting $t=tan(x/2)$, which transforms the equation into
$$
A+frac4Dt^2(1+t^2)^2=frac2Bt1+t^2+fracC(1-t^2)1+t^2
$$
which is what you did. As you see, this generally is a quartic:
$$
(A+C)t^4-2Bt^3+(2A+4D)t^2-2Bt-C=0
$$



One gets a symmetry when $B=0$, because in this case the parabola is symmetric with respect to the $X$-axis: as you see, the quartic becomes biquadratic.






share|cite|improve this answer





















  • @ egreg: Thanks for the detailed explanation. I also tried $A^2=A^2cos^2x+A^2sin^2x$ with reordering the terms, but without success. Hence, there is no way to simplify the equation :-(
    – justik
    14 hours ago










Your Answer




StackExchange.ifUsing("editor", function ()
return StackExchange.using("mathjaxEditing", function ()
StackExchange.MarkdownEditor.creationCallbacks.add(function (editor, postfix)
StackExchange.mathjaxEditing.prepareWmdForMathJax(editor, postfix, [["$", "$"], ["\\(","\\)"]]);
);
);
, "mathjax-editing");

StackExchange.ready(function()
var channelOptions =
tags: "".split(" "),
id: "69"
;
initTagRenderer("".split(" "), "".split(" "), channelOptions);

StackExchange.using("externalEditor", function()
// Have to fire editor after snippets, if snippets enabled
if (StackExchange.settings.snippets.snippetsEnabled)
StackExchange.using("snippets", function()
createEditor();
);

else
createEditor();

);

function createEditor()
StackExchange.prepareEditor(
heartbeatType: 'answer',
convertImagesToLinks: true,
noModals: false,
showLowRepImageUploadWarning: true,
reputationToPostImages: 10,
bindNavPrevention: true,
postfix: "",
noCode: true, onDemand: true,
discardSelector: ".discard-answer"
,immediatelyShowMarkdownHelp:true
);



);








 

draft saved


draft discarded


















StackExchange.ready(
function ()
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f2872808%2fcan-we-solve-ad-sin2x-b-sin-xc-cos-x-without-having-to-solve-a-quartic-po%23new-answer', 'question_page');

);

Post as a guest






























1 Answer
1






active

oldest

votes








1 Answer
1






active

oldest

votes









active

oldest

votes






active

oldest

votes








up vote
1
down vote













If you set $X=cos x$ and $Y=sin x$, the equation becomes geometrically finding the intersection of $DY^2-CX-BY-A=0$ (a parabola when $Dne0$), with the circle $X^2+Y^2=1$, which generally has four solutions. So, no: you can't reduce the resolvent equation from degree $4$ unless there is some particular relation between the coefficients.



If $D=0$ the problem becomes intersecting a line (provided one among $B$ and $C$ is nonzero) with a circle and indeed can be reduced to a quadratic equation.



It's no better if you use $A=Acos^2x+Asin^2x$, because the conic becomes
$$
AX^2+(A-D)Y^2+CX+BY=0
$$
which is either an ellipse, for $A(A-D)>0$, or a hyperbola, for $A(A-D)<0$.



Another way to see it is setting $t=tan(x/2)$, which transforms the equation into
$$
A+frac4Dt^2(1+t^2)^2=frac2Bt1+t^2+fracC(1-t^2)1+t^2
$$
which is what you did. As you see, this generally is a quartic:
$$
(A+C)t^4-2Bt^3+(2A+4D)t^2-2Bt-C=0
$$



One gets a symmetry when $B=0$, because in this case the parabola is symmetric with respect to the $X$-axis: as you see, the quartic becomes biquadratic.






share|cite|improve this answer





















  • @ egreg: Thanks for the detailed explanation. I also tried $A^2=A^2cos^2x+A^2sin^2x$ with reordering the terms, but without success. Hence, there is no way to simplify the equation :-(
    – justik
    14 hours ago














up vote
1
down vote













If you set $X=cos x$ and $Y=sin x$, the equation becomes geometrically finding the intersection of $DY^2-CX-BY-A=0$ (a parabola when $Dne0$), with the circle $X^2+Y^2=1$, which generally has four solutions. So, no: you can't reduce the resolvent equation from degree $4$ unless there is some particular relation between the coefficients.



If $D=0$ the problem becomes intersecting a line (provided one among $B$ and $C$ is nonzero) with a circle and indeed can be reduced to a quadratic equation.



It's no better if you use $A=Acos^2x+Asin^2x$, because the conic becomes
$$
AX^2+(A-D)Y^2+CX+BY=0
$$
which is either an ellipse, for $A(A-D)>0$, or a hyperbola, for $A(A-D)<0$.



Another way to see it is setting $t=tan(x/2)$, which transforms the equation into
$$
A+frac4Dt^2(1+t^2)^2=frac2Bt1+t^2+fracC(1-t^2)1+t^2
$$
which is what you did. As you see, this generally is a quartic:
$$
(A+C)t^4-2Bt^3+(2A+4D)t^2-2Bt-C=0
$$



One gets a symmetry when $B=0$, because in this case the parabola is symmetric with respect to the $X$-axis: as you see, the quartic becomes biquadratic.






share|cite|improve this answer





















  • @ egreg: Thanks for the detailed explanation. I also tried $A^2=A^2cos^2x+A^2sin^2x$ with reordering the terms, but without success. Hence, there is no way to simplify the equation :-(
    – justik
    14 hours ago












up vote
1
down vote










up vote
1
down vote









If you set $X=cos x$ and $Y=sin x$, the equation becomes geometrically finding the intersection of $DY^2-CX-BY-A=0$ (a parabola when $Dne0$), with the circle $X^2+Y^2=1$, which generally has four solutions. So, no: you can't reduce the resolvent equation from degree $4$ unless there is some particular relation between the coefficients.



If $D=0$ the problem becomes intersecting a line (provided one among $B$ and $C$ is nonzero) with a circle and indeed can be reduced to a quadratic equation.



It's no better if you use $A=Acos^2x+Asin^2x$, because the conic becomes
$$
AX^2+(A-D)Y^2+CX+BY=0
$$
which is either an ellipse, for $A(A-D)>0$, or a hyperbola, for $A(A-D)<0$.



Another way to see it is setting $t=tan(x/2)$, which transforms the equation into
$$
A+frac4Dt^2(1+t^2)^2=frac2Bt1+t^2+fracC(1-t^2)1+t^2
$$
which is what you did. As you see, this generally is a quartic:
$$
(A+C)t^4-2Bt^3+(2A+4D)t^2-2Bt-C=0
$$



One gets a symmetry when $B=0$, because in this case the parabola is symmetric with respect to the $X$-axis: as you see, the quartic becomes biquadratic.






share|cite|improve this answer













If you set $X=cos x$ and $Y=sin x$, the equation becomes geometrically finding the intersection of $DY^2-CX-BY-A=0$ (a parabola when $Dne0$), with the circle $X^2+Y^2=1$, which generally has four solutions. So, no: you can't reduce the resolvent equation from degree $4$ unless there is some particular relation between the coefficients.



If $D=0$ the problem becomes intersecting a line (provided one among $B$ and $C$ is nonzero) with a circle and indeed can be reduced to a quadratic equation.



It's no better if you use $A=Acos^2x+Asin^2x$, because the conic becomes
$$
AX^2+(A-D)Y^2+CX+BY=0
$$
which is either an ellipse, for $A(A-D)>0$, or a hyperbola, for $A(A-D)<0$.



Another way to see it is setting $t=tan(x/2)$, which transforms the equation into
$$
A+frac4Dt^2(1+t^2)^2=frac2Bt1+t^2+fracC(1-t^2)1+t^2
$$
which is what you did. As you see, this generally is a quartic:
$$
(A+C)t^4-2Bt^3+(2A+4D)t^2-2Bt-C=0
$$



One gets a symmetry when $B=0$, because in this case the parabola is symmetric with respect to the $X$-axis: as you see, the quartic becomes biquadratic.







share|cite|improve this answer













share|cite|improve this answer



share|cite|improve this answer











answered 15 hours ago









egreg

164k1179187




164k1179187











  • @ egreg: Thanks for the detailed explanation. I also tried $A^2=A^2cos^2x+A^2sin^2x$ with reordering the terms, but without success. Hence, there is no way to simplify the equation :-(
    – justik
    14 hours ago
















  • @ egreg: Thanks for the detailed explanation. I also tried $A^2=A^2cos^2x+A^2sin^2x$ with reordering the terms, but without success. Hence, there is no way to simplify the equation :-(
    – justik
    14 hours ago















@ egreg: Thanks for the detailed explanation. I also tried $A^2=A^2cos^2x+A^2sin^2x$ with reordering the terms, but without success. Hence, there is no way to simplify the equation :-(
– justik
14 hours ago




@ egreg: Thanks for the detailed explanation. I also tried $A^2=A^2cos^2x+A^2sin^2x$ with reordering the terms, but without success. Hence, there is no way to simplify the equation :-(
– justik
14 hours ago












 

draft saved


draft discarded


























 


draft saved


draft discarded














StackExchange.ready(
function ()
StackExchange.openid.initPostLogin('.new-post-login', 'https%3a%2f%2fmath.stackexchange.com%2fquestions%2f2872808%2fcan-we-solve-ad-sin2x-b-sin-xc-cos-x-without-having-to-solve-a-quartic-po%23new-answer', 'question_page');

);

Post as a guest













































































Comments

Popular posts from this blog

What is the equation of a 3D cone with generalised tilt?

Color the edges and diagonals of a regular polygon

Relationship between determinant of matrix and determinant of adjoint?